2020
DOI: 10.21203/rs.3.rs-68034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecology of inorganic sulfur auxiliary metabolism in widespread bacteriophages

Abstract: Microbial sulfur metabolism contributes to biogeochemical cycling on global scales. Sulfur metabolizing microbes are infected by phages that can encode auxiliary metabolic genes (AMGs) to alter sulfur metabolism within host cells but remain poorly characterized. Here we identified 191 phages derived from twelve environments that encoded 227 AMGs for oxidation of sulfur and thiosulfate (dsrA, dsrC/tusE, soxC, soxD and soxYZ). Evidence for retention of AMGs during niche-differentiation of diverse phage populatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Few eukaryotic viruses may be related to the ltering operation in the virus enrichment process. Interestingly, we found that a large proportion of viral AMGs was involved in sulfur metabolism, in agreement with recent reports that the viruses are widely participants in both organic and inorganic sulfur metabolism in human gut [34,35]. The sul de provides a tness advantage to viruses and viruses also are drivers of organosulfur metabolism with important implications for human health [34].…”
Section: Discussionsupporting
confidence: 91%
“…Few eukaryotic viruses may be related to the ltering operation in the virus enrichment process. Interestingly, we found that a large proportion of viral AMGs was involved in sulfur metabolism, in agreement with recent reports that the viruses are widely participants in both organic and inorganic sulfur metabolism in human gut [34,35]. The sul de provides a tness advantage to viruses and viruses also are drivers of organosulfur metabolism with important implications for human health [34].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, viruses carrying dsrC genes, which are involved in dissimilatory sulfate reduction, were found in Saanich Inlet that putatively infect SUP05 bacteria (Roux et al, 2014). AMGs putatively involved in sulfite oxidation, soxY, have also been observed in the ETSP (Kieft et al, 2021). Additionally, viruses carrying putative AMGs from nitrogen cycle pathways have been observed in OMZs such as amoC, which encodes for ammonia monooxygenase subunit C involved in nitrification, nirK, which encodes for a Cu-containing nitrite reductase involved in denitrification, and norB, which encodes for a nitric oxide reductase involved in denitrification (Ahlgren et al, 2019;GazitĂșa et al, 2021).…”
Section: Virusesmentioning
confidence: 99%
“…One such mechanism involves viruses ''stealing'' metabolic genes from their host in order to gain fitness advantages during infection (Sullivan et al, 2006). Such host-derived viral genes are termed auxiliary metabolic genes (AMGs) and are expressed during infection to modulate microbial respiration, biosynthesis processes, and/or direct intracellular nutrients toward virus replication and virion production (Anantharaman et al, 2014;Breitbart et al, 2007;Hurwitz et al, 2013Hurwitz et al, , 2015Kieft et al, 2021;Mann et al, 2003;Roux et al, 2014;Suttle, 2005;Thompson et al, 2011;Trubl et al, 2018). For example, some viruses of Cyanobacteria encode core photosystem proteins that augment host metabolism in order to increase the biosynthesis of dNTPs that are utilized for viral genome replication (Thompson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%